Implementation of an Intravenous Fluid Titration Algorithm to Treat Pediatric Diabetic Ketoacidosis - Babbitt, Christopher; Dadios, Marc; Chau, Ariya; Tse, Graham; Brown, Lisa; Ladbury, Tracy; Morphew, Tricia; Brakin, Mario (Journal of Pediatric Intensive Care, 2020)
Diabetic ketoacidosis (DKA) is a common cause of admission to the pediatric intensive care unit and many centers utilize the “two-bag system” to treat DKA. We developed an intravenous fluid (IVF) titration algorithm to standardize adjustments of the two bags. A retrospective cohort study was performed comparing 155 patients treated before and 175 patients treated after implementation of the IVF titration algorithm. Postimplementation patients reached the blood glucose target zone faster and had a higher probability of remaining at goal while on insulin infusion. There was no significant difference in incidence of cerebral edema or hypoglycemia between study groups. Overall IVF titration algorithm compliance was 95%. Implementation of an IVF titration algorithm is safe and effective when treating DKA in children.
Keywords: diabetes; insulin; ketoacidosis